John D. Roberts: In His Own Words and Those of His Friends1. Issue 52 (21st September 2015) - Seeman, Jeffrey I.
Abstract: In honor of the 97th birthday of Professor John D. Roberts, the author has assembled a collection of poignant quotes and anecdotes, mostly written by Roberts himself, which embody his philosophies of life and his wide‐ranging experiences and interests. A brief summary of Roberts's major scientific accomplishments is also presented. Abstract : A 20th century pioneer in physical organic chemistry, John D. Roberts celebrated his 97th birthday in 2015. To mark this occasion, poignant quotes and anecdotes have been collected embodying his philosophies of life and his wide‐ranging experiences and interests. A brief summary of Roberts's major scientific accomplishments is also presented. Photograph courtesy John D. Roberts.